Some remaining problems and solutions for them in establishment of industrial property rights in Vietnam - Minh, Khong Quoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Intellectual properties in general and industrial properties (IP) in particular are efficient tools for socio-economic development. Exclusivity is the key content of legal regulations for protection of industrial property rights. It creates high competitive potentials and, at the same time, encourages social actors to make more new IP creativities for exclusive rights to protection. However, the time for examination of applications for establishment of IP rights is long actually in Vietnam and the low quality of applications cause impacts production and business activities of enterprises. The first part of the paper deals with the role of establishment of IP rights in socio-economic development. The next part of the paper provides analysis and remarks some remaining problems and reasons in aspects of establishment of IP rights; trends of development of activities of establishment of IP rights in the world. The last part deals with solutions proposed for higher effectiveness of activities of establishment of IP rights in Vietnam. This paper is the research result by the author through analysis of documents, in-depth interviews of experts in authority institutions, management agencies and enterprises. The scope of applications dealt in the paper is of national trademarks, inventions, utilities and industrial designs.